Clinical gynecologic oncology - Di Saia, Philip J; Creasman, William T (Mosby, 2002)
Univ. of California, Irvine. Brandon/Hill Medical List selection (#228). Practical, clinical reference for residents and clinicians. This edition contains a color atlas of key gross and microscopic specimens. Key points are highlighted. Previous edition: c1997. Helpful appendices are also included.
Keywords: gynekologie a porodnictví; onkologie; nádory ženských pohlavních orgánů; gynekologická onemocnění; Genital Neoplasms, Female; Genital Diseases, Female